Analisis Green Restaurant pada Pool and Beach Restaurant - Pradnyan, Made Satya; Widhyadanta, I Gede Dirga Surya Arya; Rinayanthi, Ni Made (Institut Pariwisata dan Bisnis Internasional, 2024)
Green Restaurant Association (GRA) merupakan pedoman dalam penerapan Green Restaurant di United State of America yang telah berdiri sejak tahun 1990, Peran GRA sangat penting dalam mempelopori gerakan Green Restaurant di dunia perindustrian, yang bertujuan untuk menghijaukan operasional dengan menggunakan standar sertifikasi. Pool and Beach Restaurant di Faena Hotel Miami Beach yang melalui observasi awal memiliki potensi dan sangat menarik untuk diteliti dalam meraih Green Restaurant. Penelitian ini dilakukan di Faena Hotel Miami Beach dengan teknik pengumpulan data melalui wawancara yang mendalam dengan pihak-pihak hotel yang menguasai bidangnya, observasi/pengamatan, dan dokumentasi, yang dianalisis dengan teknik analisis deskriptif kualitatif. Hasil penelitian dari 7 indikator utama yaitu: Energy, Water Efficiency, Waste Reduction & Recycling, Reusables & Environmentally Preferable Disposables, Chemicals & Pollution Reduction, Building Materials, dan Sustainable Food, yang masing-masing memiliki sub-indikator sehingga menjadi 13 indikator menunjukan bahwa 82% Sesuai dengan indikator dan 18% Tidak Sesuai dengan indikator GRA. The Green Restaurant Association (GRA) is a guideline in implementing Green Restaurant in the United State of America which has been established since 1990. GRA's role is very important in pioneering the Green Restaurant movement in the industrial world, which aims to green operations by using certification standards. Pool and Beach Restaurant at Faena Hotel Miami Beach which through observation has potential and is very interesting to research in achieving Green Restaurant. This research was conducted at the Faena Hotel Miami Beach with data collection techniques through in-depth interviews with hotel parties who master their fields, observation, and documentation, which were analyzed using qualitative descriptive analysis techniques. The result is researched with 7 main indicators, they are: Energy, Water Efficiency, Waste Reduction & Recycling, Reusables & Environmentally Preferable Disposables, Chemicals & Pollution Reduction, Building Materials, and Sustainable Food, each of which has sub-indicators there are 13 indicators in total, showing that 82% In accordance and 18% Not in accordance with the indicators of GRA.